Perioperative Management of Target-Specific Oral Anticoagulants. Issue 1 (February 2014) - Bergmark, Brian; Giugliano, Robert P.
Abstract : : Target-specific oral anticoagulants (TSOACs), which offer rapid onset and more predictable pharmacokinetics/dynamics compared with vitamin K antagonists, are rapidly growing in number and approved indications. At least 1 in 10 Americans receiving outpatient anticoagulant therapy requires interruption of anticoagulation for an invasive procedure annually, and management of these new agents in the perioperative setting is made challenging by difficulty measuring anticoagulant effect and the lack of effective reversal. Surgical planning must account for individual patient risks for bleeding and thrombosis, the type of procedure, and expected drug clearance. Based upon these considerations, a perioperative plan encompassing timing of TSOAC cessation and resumption, as well as bridging therapy, if needed, can be developed. Perioperative strategies remain largely predicated on extrapolations from pharmacokinetics and expert opinion, though a growing body of literature is providing greater guidance in this important area.